Pengaruh Penerapan Akuntansi Lingkungan dan Ukuran Perusahaan terhadap Profitabilitas Serta Pengungkapan Informasi Lingkungan sebagai Variabel Intervening - Reska Dwicahyanti; Hero Priono (CV. Syntax Corporation Indonesia, 2021)
In this industry 4. 0 era, the company's requirements are not only concentrated on the owner and management, but also on all aspects, such as consumers, employees, society and the environment. This kind of thinking is based on the company and is related to the interests of certain aspects such as the environment. This is because the environmental aspects will be useful to the communities around the company that have a long-term impact. This research is a type of quantitative research. The sampling technique adopts the purpose sampling method. The data used in this research comes from the financial statements and annual reports of companies that follow the IDX registration and follow the appropriate period of 2018-2019. This hypothesis was tested by using the guided trap parameter estimation method of SmartPLS 3. 0 data analysis tool. The research results show that company size and CSRi variables have a significant impact on profitability. The size of a company will seriously affect profitability; CSRi significantly affects profitability, and CSRi significantly mediates the impact of green accounting and company size on profitability